IκB-kinaseβ-dependent NF-κB activation provides radioprotection to the intestinal epithelium - Egan, Laurence J. (National Academy of Sciences, 2004)
Acute injury to the intestinal mucosa is a major dose-limiting complication of abdominal radiation therapy. We studied the role of the transcription factor NF-κB in protection against radiation-induced apoptosis in the intestinal epithelium in vivo. We use mice in which NF-κB signaling through IκB-kinase (IKK)-β is selectively ablated in intestinal epithelial cells to show that failure to activate epithelial cell NF-κB in vivo results in a significant increase in radiation-induced epithelial cell apoptosis. Furthermore, bacterial lipopolysaccharide, which is normally a radioprotective agent, is radiosensitizing in IKKβ-deficient intestinal epithelial cells. Increased apoptosis in IKKβ-deficient intestinal epithelial cells was accompanied by increased expression and activation of the tumor suppressor p53 and decreased expression of antiapoptotic Bcl-2 family proteins. These results demonstrate the physiological importance of the NF-κB system in protection against radiation-induced death in the intestinal epithelium in vivo and identify IKKβ as a key molecular target for radioprotection in the intestine. Selective preactivation of NF-κB through IKKβ in intestinal epithelial cells could provide a therapeutic modality that allows higher doses of radiation to be tolerated during cancer radiotherapy.